Exaggerated blood pressure response to early stages of exercise stress testing and presence of hypertension. Issue 12 (December 2016) - Schultz, Martin G.; Picone, Dean S.; Nikolic, Sonja B.; Williams, Andrew D.; Sharman, James E.
Abstract: Objectives: Exaggerated exercise blood pressure (EEBP) recorded during exercise testing at moderate-intensity is independently associated with cardiovascular mortality. It is hypothesized that EEBP may be indicative of underlying hypertension unnoticed by standard clinic (resting) BP measures (thus explaining increased mortality risk), but this has never been confirmed by association with hypertension defined using ambulatory BP monitoring, which was the aim of this study. Design: Cross-sectional study. Methods: 100 consecutive patients free from coronary artery disease (aged 56 ± 9 years, 72% male) underwent clinically indicated exercise stress testing. Exercise BP was recorded at each stage of the Bruce protocol. Presence of hypertension was defined as 24-hour systolic BP ≥130 mmHg or daytime systolic BP ≥135 mmHg. Results: Exercise systolic BP at stage 1 and 2 of the test was significantly associated with the presence of hypertension ( P  < 0.05), with the strongest association observed between stage 1 exercise systolic BP and 24-h systolic BP >130 mmHg (AUC = 0.752, 95% CI's 0.649–0.846, P  < 0.001). 79% of participants achieving systolic BP ≥150 mmHg at stage 1 of the test were classified as having hypertension, with systolic BP >150 mmHg predicting hypertension independently of age, sex and in-clinic hypertension status (OR = 4.83, 95% CI's 1.62–14.39, P  = 0.005). Conclusions: Irrespective of resting BP, systolic BP ≥150 mmHg during early stages of the Bruce exercise stress test is associated with presence of hypertension. EEBP should be a warning signal to health/exercise professionals on the presence of hypertension and the need to provide follow up care to reduce cardiovascular risk.